Contribution of Women’s Working Time on Vegetable Crops to Family Income in Ogan Komering Ulu District - Bastari, Eka Yulia; Oktarina, Yetty; Efrianti, Rini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
The purpose of this study was to analyze the income of female farmers on family income in Ogan Komering Ulu Regency. The method used in this study is the survey method. The sampling method in this study was carried out in proportion randomly with a sample of 180 female farmers. The results obtained explained that the outpouring of women's work time <0.40 Perso with the number of respondents as many as 28 people (15.56%), 0.41-0.50 HOK (labor working day) as many as 38 people (21.11%), 0.61-0.70 HOK as many as 88 people (48.89%) and 0.71-0.80 HOK as many as 26 people (14.44%). Based on the outpouring of women's working time in Ogan Komering Ulu Regency is 0.61-0.70 HOK with a total of 88 respondents (48.89%). The contribution of women farmers to family income in Semidang Aji District is 25.94%. The contribution of women farmers to family income in Sosoh Buay Rayap District was 25.67% and the contribution of female farmers to family income in Lubuk Raja District was 26.62%. Then the contribution of women farmers to family income is the highest contribution of women's income in Lubuk Raja District at 26.62%. The contribution of women farming vegetable crops to family income in Ogan Komering Ulu Regency was 26.08%. this shows that more than a quarter of the income of peasant families comes from female farmers. So women farmers contribute quite a lot to the total income of the farmer's family. The income is used to meet the needs of the family such as daily food expenses, school fees for children, and so on.